Effect of recovery duration on intermittent tennis drills - Ferrauti, A.; Weber, K. (2001)
We examined the effects of recovery duration on the running speed and stroke quality of elite tennis players, during intermittent on-court sprint exercises. Ten nationally ranked male players participated in an exercise designed to improve starting speed and acceleration in combination with a tennis stroke under maximum time pressure. Standardisation (rest periods between strokes, time pressure and stroke situation) was assured by the use of a ball-machine. Time pressure for stroke preparation corresponded to 81.9 +/- 4.8% of the maximum running speed. On two randomised occasions (A and B) separated by two weeks, players completed 30 (6 x 5) stroke/sprints. The rest period between each stroke/sprint was 10 seconds on occasion A and 15 seconds on occasion B. Results: With the short rest period (A), blood lactate concentration was significantly elevated (9.04 +/-3.06 versus 5.01 +/-1.35 mmol/l) and the running time required for stroke preparation was significantly increased (1.405 +/- 0.044 seconds versus 1.376 +/- 0.045 seconds). Stroke velocity decreased on occasion A (105.6 +/- 11.80 versus 114.4 +/- 7.5 km/h), while stroke precision tended to be higher. We concluded that precautions should be taken in intermittent exercises to avoid high blood lactate acidosis. When maximum workload intensity is required, the training efficiency for running speed and skill levels can only be maintained with the aid of a sufficient rest period (i.e. a minimum of 15 seconds rest after 2 seconds of maximum workload).